The Impact of Financial Ratios on Profit Growth of Public Health Sector Companies - Yustisia, Natali; Indrienny, Sahhara (Management Research Studies Journal, 2024)
The purpose of this research is to determine the influence of  Debt to Asset Ratio, Total Asset Turnover, and Return on Asset on the profit growth of public healthcare sector companies listed on the Indonesia Stock Exchange during the period of 2017-2021. The population of this study consists of public healthcare sector companies listed on the Indonesia Stock Exchange. The sample was determined using purposive sampling technique, and the selected sample consists of 3 public healthcare sector companies. The data analysis technique used in this research is panel data regression analysis with the assistance of EViews 12 software. The research findings indicate that the variable Debt to Asset Ratio does not have a significant influence on profit growth, Total Asset Turnover has a significant negative influence on profit growth, while the variable Return on Asset has a significant positive influence on profit growth. Keywords: Debt to Asset Ratio, Total Asset Turnover, Return on Asset, profit growth,                healthcare sector